Firm-level indicators of instrumental and political CSR processes – A multiple case study. Issue 2 (April 2021) - Richter, Ulf Henning; Shirodkar, Vikrant; Shete, Namita
Abstract: Recent studies have been increasingly distinguishing between instrumental and political approaches to corporate social responsibility (CSR). However, few studies have explored the firm-level processes generating these types of CSR engagements. Using Basu and Palazzo's (2008) proposition to model CSR as a process of sensemaking, we suggest that multinational enterprises use different processes in developing capabilities around instrumental and political CSR. Our qualitative multiple case–study analysis is based on data from 42 in-depth, semi-structured interviews with 27 senior managers from British American Tobacco, Nestlé, and Hewlett Packard. Our findings from the three cases indicate that instrumental and political CSR are characterised by different sensemaking processes. We also find evidence for overlapping of processes between instrumental and political CSR.